History, design, and legacy : architectural prizes and medals : an academic investigation of the Royal Institute of British Architects' royal gold medal /: architectural prizes and medals : an academic investigation of the Royal Institute of British Architects' royal gold medal. (2019) - Walder, Liz
No abstract available